Transmembrane Fluoride Transport by a Cyclic Azapeptide With Two β-Turns - Zhao, Zhixing; Zhang, Miaomiao; Tang, Bailing; Weng, Peimin; Zhang, Yueyang; Yan, Xiaosheng; Li, Zhao; Jiang, Yun-Bao (Frontiers in Chemistry, 2021)
Diverse classes of anion transporters have been developed, most of which focuses on the transmembrane chloride transport due to its significance in living systems. Fluoride transport has to some extent been overlooked despite the importance of fluoride channels in bacterial survival. Here we report the design and synthesis of a cyclic azapeptide (a peptide-based N-amidothiourea, 1), as a transporter for fluoride transportation through a confined cavity that encapsulates fluoride, together with acyclic control compounds, the analogues 2 and 3. Cyclic receptor 1 exhibits more stable β-turn structures than the control compounds 2 and 3, and affords a confined cavity containing multiple inner –NH protons that serve as hydrogen bond donors to bind anions. It is noteworthy that the cyclic receptor 1 shows the capacity to selectively transport fluoride across lipid bilayer, on the basis of the osmotic and fluoride ion-selective electrode (ISE) assays, during which an electrogenic anion transport mechanism is found operative, whereas no transmembrane transport activity was found with 2 and 3, despite that 2 and 3 are also able to bind fluoride via the thiourea moieties. These results demonstrate that the encapsulation of anionic guest within a cyclic host compound is key to enhance the anion transport activity and selectivity.